Realizing a healthy pregnancy through optimizing the participation in pregnant women class - Fitriana Ikhtiarinawati Fajrin; Naila Shofa Nida’ul Khusna (Community Empowerment, 2021)
This community service aims to increase knowledge, change attitudes and behavior of mothers to understand pregnancy, body changes, complaints during pregnancy, pregnancy care, childbirth, postpartum care, postnatal family planning, newborn care, and myths to achieve a healthy pregnancy. The method of the community service is health education in the form of pregnant women class and demonstrations of pregnant gymnastics practices which are carried out at the Sumberagung Village Hall, Sukodadi District, Lamongan Regency. The results indicate an increase in knowledge of pregnant women related to information about pregnancy and childbirth. Thus, pregnant women have an awareness of the importance of taking classes for pregnant women and make it a necessity to realize a healthy pregnancy.